2010
DOI: 10.1111/j.1469-0691.2009.03086.x
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous pneumomediastinum complicating pneumonia in children infected with the 2009 pandemic influenza A (HINI) virus

Abstract: We report two occurrences of spontaneous pneumomediastinum (SPM) complicating pneumonia in Japanese children infected with the novel influenza A (H1N1) virus (IV). General practitioners especially should suspect possible SPM when examining and treating children with the novel influenza accompanied by status asthmaticus or wheezing. The presented patients illustrate the specific clinical and radiological signs associated with SPM complicating pneumonia in children infected with A(H1N1)v.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 14 publications
2
34
0
Order By: Relevance
“…Spontaneous pneumomediastinum following influenza H1N1 virus infection is extremely rare and in literature there are a few reports on this association [2,[5][6]. To the best of our knowledge, at the moment, this is the first case of pneumorrachis associated with H1N1 infection, while no association with other influenza virus infection is reported in literature.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Spontaneous pneumomediastinum following influenza H1N1 virus infection is extremely rare and in literature there are a few reports on this association [2,[5][6]. To the best of our knowledge, at the moment, this is the first case of pneumorrachis associated with H1N1 infection, while no association with other influenza virus infection is reported in literature.…”
Section: Discussionmentioning
confidence: 74%
“…The novel influenza A H1N1 virus was identified as the main cause of the sudden outbreak of several febrile respiratory infections ranging from selflimited to severe illness both in children and adults. Children may be more liable to catch an H1N1 infection presenting with fever, violent cough, dyspnea, and bilateral patchy pulmonary shadows upon the inspection of the chest radiograph [2]. Moreover, when patients are younger than 2 years of age they are at higher risk of being hospitalized [3].…”
Section: Introductionmentioning
confidence: 99%
“…2 Although there is a wellestablished link between underlying respiratory illnesses, especially asthma, and spontaneous pneumomediastinum, 3,4 our experience with the three patients we have described supports the association of pandemic (H1N1) influenza with air leak syndrome, including pneumomediastinum, and subcutaneous and prevertebral emphysema in a different pediatric population.…”
Section: Key Pointsmentioning
confidence: 84%
“…2 The patients were six and eight years of age, and neither had a history of asthma. Soto-Abraham and coworkers reported that pathologic features of fatal pandemic (H1N1) influenza included hemorrhage and necrosis of the upper respiratory tract and necrosis of the bronchiolar walls.…”
mentioning
confidence: 99%
“…Up till now there have been no reported cases of pneumomediastinum complicating pneumonia in adolescents by a novel swine origin influenza A (H1N1). Only Hasegawa et al 6 has reported 2 patients who have had asthma or asthmatic symptoms. Our patient, though, showed unusual clinical signs such as blood tinged sputum and no wheezing, radiologic signs that are typical of pneumomediastinum with pneumonia.…”
Section: Discussionmentioning
confidence: 99%